A rapid method of gene detection using DNA bound to Sephacryl. - Langdale, J; Malcolm, A (1985)
A rapid method of gene detection has been developed utilising DNA fragments immobilized on resins and a sandwich hybridization assay. This method permits the detection of restriction fragment length polymorphisms (RFLPs) without the need to immobilize sample DNA. The method is based on the use of two non-overlapping DNA restriction fragments, one of which is attached to a resin (fragment A) and the other 32P-labelled (fragment B). Fragments A and B will not hybridize to each other unless there is a DNA or RNA fragment capable of hybridizing to both A and B present in the same reaction. Hybridization in this instance will result in the resin being radioactively labelled. The RFLP associated with the mutation causing sickle-cell anaemia was used as a model to develop the method. The resin Sephacryl S-500 appeared most suited to our method for two reasons: (i) DNA immobilization experiments using two coupling procedures and four resins indicated that Sephacryl S-500 bound the most DNA with very little non-covalent coupling. (ii) Hybridization experiments with DNA bound to a number of resins showed that DNA bound to Sephacryl S-500 hybridized most efficiently with a low level of nonspecific hybridization. Using optimum hybridization conditions 5 X 10(-18) mol of beta-globin DNA could be detected. The method has been used to distinguish between DNA from sickle, heterozygote and normal patients.